Animality. - Hofman, Jens; Agamben, Giorgio; Levinas, Emmanuel; Deleuze, Gilles; Guattari, Félix; Foucault, Michel; Bataille, Georges; Nietzche, Friedrich (Marian Goodman gallery : New York, 2016)
Allora and Calzadilla; Baldessari, John; Balkenhol, Stephan; Bismuth, Pierre; Von Bonin, Cosima; Broodthaers, Marcel; Burkhard, Balthasar; Cattelan, Maurizio; Cruzvillegas, abraham; De Bruyckere, berlinde; Dion, Mark; Dürer, Alfred; Ethridge, Roe; Halilaj, Petrit; Horn, Rony; Hujar, Peter; Jones, Sarah; Kilimnik, Karen; Lawler, louise; Lempert, Jochen; Liden, Karen; Shwky, Wael; Vo, Danh; Sundblad, Emily
Animality, Marian Goodman Gallery, London, 3 november -17 december 2016
boek